Role of Visual Evoked Potentials in Multiple Sclerosis - Thame, Ammar A.; Mohammed, Najeeb H.; Ibrahim, Akram M. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Multiple sclerosis (MS) is a chronic, demyelinating disease of the central nervous system (CNS) affecting young adults and is considered as the leading cause of non traumatic neurological disability of young adults affecting nearly 2 million people worldwide. The pathogenesis of MS is at best incompletely understood. There are several proposed mechanisms that may be important in the production of MS plaques: autoimmunity, environment and heredity. Deviation of immune responses in a genetically susceptible patient plays a central role in its pathogenesis. Electrophysiological, spinal tap and Radiological tools are important laboratory investigations and have added so much to the clinical diagnosis and for the classification of MS. It was found that visual function and conduction has been changed in patients with multiple sclerosis.Objectives: The aims of the study is to estimate and evaluate the visual evoked potential (VEP) parameters in patients with MS and its relation to their disability degree (using the expanded disability status scale score "EDSS") and visual presentation of them in comparison with healthy individuals.Patients and Methods: 112 patients with multiple sclerosis and 50 subjects without any neurological or psychiatric diseases as control group were recruited in this study. The cases were collected from Baghdad teaching hospital, MS center, Baghdad, Iraq at the period from May 2012 to April 2013, and studied at the unit of electrophysiology in Al-Shaheed Ghazi Al-Hareri Hospital in the Medical city. All patients and control groups were tested for VEP.Results: The present study showed a significant increase in the P100 latency and inter-ocular (IO) latency difference and non statistical significant decrease in the IO amplitude difference in patients group than the control group. Also among patients group there was positive linear correlation between the severity of the disease measured by EDSS score and P100 latency while negative linear correlation with the amplitude. Conclusion: There was a higher percent of patients with defective VEP parameters and so their visual pathway even if it was asymptomatic, in addition to their relation with patients` disability than the control group, making it easy to quantify and predict MS disability objectively. Keywords: Multiple sclerosis, Expanded Disability Status Scale, VEP.